Challenges to balance food demand and supply: analysis of PNAE execution in one semiarid region of Brazil - Chaves, Viviany Moura; Pinheiro, Liana Galvão Bacurau; Neves, Renata Alexandra Moreira das; Araújo, Maria Arlete Duarte de; Silva, Joana Barbosa da; Bezerra, Paulo Eneas Rolim; Jacob, Michelle Cristine Medeiros (Desenvolvimento e Meio Ambiente, 2020)
This study intended to address the challenges faced by the National School Feeding Program (PNAE) to implement public purchases from family farming, as they understand their role in the transformation of local food systems. For this, we developed a qualitative, exploratory, and descriptive study, in the state of Rio Grande do Norte, located in the northeastern semiarid region, during the regional assessments done by the Collaborating Center for the School Feeding Program in 2018 and 2019. We analyzed the policy from the perspective of the social actors inserted at the ends of the supply and demand chain through the application of questionnaires and focus groups. There were 188 social actors from 45 municipalities taking part in our data gathering. We examined the meeting of supply and demand based on the performance of the policy in the state, and identified that: i) the percentage of purchases between 2011 and 2017 was, on average, 19.1%, demonstrating that, despite not meeting the recommended rate, the state has progressed its investments in this segment; ii) some limitations characterized the limited effectiveness of public purchases of family farming for schools: lack of federal actions to enhance the value of family farming, unfavorable conditions for local agricultural production, low performance of technical rural assistance, menus do not reflect the offer of family farming, difficulties in preparing and executing the public call and insufficient communication between social actors; iii) Action and decision-making, through street-level bureaucracy, depends on the discretion of the social actors. We believe that this study can collaborate in the understanding of structural problems that affect the implementation of the program and assist in the search for alternatives that are consistent with the current needs, aiming at the construction of sustainable food systems.